The advantage using Ni - Ti rotary instruments as the smoothness of one-third apical root canal wall - Soerachman, Badi; Sukartini, Endang; Aripin, Dudi (Universitas Padjadjaran, 2014)
Canal wall preparation achieved by smoothness. Objective of this study to determine smoothness differences of nickel-titanium manual instruments compared with nickel-titanium rotary instruments in apical third region canal wall. This study was a quasi-experimental research conducted by in vitro method on 30 single rooted upper permanent incisive that have been extracted. They were randomly divided into two groups (n=15) and each group root canal teeth were cleaned and shaped with manual rotary nickel-titanium instruments. Roughness analyzed used with Mitutoyo roughness surface instruments. Every sample analyzed in third region canal wall. Data have been analyzed with a t-test. The result of the study showed that different smoothness for every sample after preparation by manual and rotary. In conclusion, from this study showed those instrumentations with rotary nickel titanium will give the best smoothness than manual nickel titanium instruments, so the result gets significantly.